Entry strategy of global corporations on the markets of non EU countries (Qatar) - Weihmann, Tom; Pichanič, Mikuláš, 1942-; Bolotov, Ilya; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
Qatar has become one of the richest countries on the planet, thanks to its abundant oil and gas reserves. These resources enable Qatar to invest in the development of its local economy and attract foreign direct investment. Numerous German companies have entered Qatar to capitalize on the country's growth. This thesis aims to provide a market entry strategy for German corporations seeking to enter the Qatari market. The theoretical part comprises a literature review, while the practical part is divided into the results of expert interviews and a SWOT analysis. The findings indicate that there are various modes of entry available to enter Qatar, but a joint venture with a Qatari partner is recommended due to its potential to mitigate cultural differences. In addition to the oil and gas sector, technology, agriculture, and public sector projects present the most promising business opportunities for German corporations.
Vedoucí práce: Mikuláš Pichanič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses